Intrinsic and extrinsic motivation : the search for optimal motivation and performance - Sansone, Carol; Harackiewicz, Judith M. (Educational psychology., 2000)
In understanding human behavior, psychologists have long been interested in what motivates specific actions. Debates have pitted extrinsic motivators (e.g. rewards/punishment) against intrinsic motivation in attempting to determine what best motivates individuals. This book provides a summary view of what research has determined about both extrinsic and intrinsic motivation, and clarifies what questions remain unanswered. Divided into three sections, section I revisits the debate about the effects of extrinsic incentives or constraints on intrinsic motivation and creativity, and identifies theoretical advances in motivational research. Section II focuses on the hidden costs and benefits of different types of achievement goals on motivation and performance. Section III discusses theory and research findings on how extrinsic and intrinsic motivators may work in everyday life and over time. This book is of interest to researchers in psychology, education, and business, as well as to a wider audience interested in promoting optimal motivation and performance. Coverage in this book includes: debates and controversies in motivational research; developmental nature of intrinsic and extrinsic motivation over time; influences of parents, educators, and employers in facilitating motivation; effect of achievement goals on learning and performance; the role of intrinsic and extrinsic motivation in self-regulation. Key features: brings together major figures in the fields of motivation, education, and social psychology; provides a mix of theory, basic and applied research; presents research conducted both in laboratories and educational settings; comprehensive chapters provide excellent reviews of previous literature as well as outlines important new directions; and provides different perspectives on controversial debates in a balanced, constructive manner.